El teletrabajo y la relación con el desempeño laboral del personal administrativo de la Universidad Nacional de Loja periodo 2020-2021 - Jaramillo Neira, Karole Daniela (2023)
The present research work aimed to establish the relationship between teleworking and the work performance of the administrative staff of the National University of Loja, period 2021-2022. Where 4 specific objectives were established: determine the evolution of the technical and legal standard of teleworking in Ecuador, establish a baseline of job performance of UNL administrative staff one year before the pandemic, determine job performance in the period 2021–2022 and finally, establish the lessons learned during teleworking to improve in future eventualities. The application method was cross-sectional, non-experimental and descriptive, for which a population of 277 was taken that correspond to the total number of administrative staff working at the National University of Loja, therefore, we obtained a sample of 161 administrative servers, where the research was carried out through surveys, interviews and observation form. It must be taken into consideration that a performance evaluation has not been carried out in the institution in 15 years. Therefore, for the baseline, a method of graphic scales proposed by Chiavenato was taken as a reference, basically it consists of evaluating performance in two aspects, such as, performance of the function (the current performance of the function was considered) and this is broken down into several factors: product, quality, knowledge of the work, cooperation; and, individual characteristics (the individual characteristics of the evaluated and their functional behavior inside and outside their function were considered) this is subdivided into: understanding of situations, creativity, ability to perform. For the graphic scale, a range from optimal (5) to bad (1) was taken into account. To evaluate work performance in teleworking, it was taken as a reference the model (with modifications) proposed by Peruvian authors Claudia Margarita Aguilar Hueso, Silvia Jumpa Correa and Lady Luz Martínez Quispe, which was carried out in your country to evaluate work performance specifically in this modality, where factors such as work performance are taken, where factors are taken such as work performance, work/family balance, job burnout, job satisfaction.